Strategi Content Writer dalam Meningkatkan Awareness dan Minat Pebisnis terhadap HashMicro melalui Artikel - Amalia Febriyani; Ika Sartika; Hudi Santoso (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital technology plays an important role in improving the competitiveness of businesses. HashMicro, as an ERP software provider, utilizes content writer strategies as part of digital marketing to increase brand awareness and attract business people to their products. This research aims to analyze the content writer strategy implemented by HashMicro in the context of B2B marketing. The method used is descriptive qualitative, with data collection through in-depth interviews, observation, and analysis of published articles. Data were analyzed using the stages of reduction, presentation, and conclusion drawing. The results showed that HashMicro integrates the AIDA principle (Attention, Interest, Desire, Action) in its content writer strategy, with a focus on keyword research, the preparation of educational and emotional articles, and the use of attractive visuals to facilitate audience understanding. In addition, SEO-optimized article writing succeeded in increasing visibility and audience engagement, thus strengthening HashMicro's position in the digital market. This research provides insight into the effectiveness of content writer strategies in increasing brand awareness and interest of business audiences and provides recommendations for other companies in optimally utilizing content marketing.